Dnmt3a-mutated clonal hematopoiesis promotes osteoporosis - Kim, Peter Geon; Niroula, Abhishek; Shkolnik, Veronica; McConkey, Marie; Lin, Amy E; Słabicki, Mikołaj; Kemp, John P; Bick, Alexander; Gibson, Christopher J; Griffin, Gabriel; Sekar, Aswin; Brooks, Daniel J; et al. (The Journal of experimental medicine, 2021)
Osteoporosis is caused by an imbalance of osteoclasts and osteoblasts, occurring in close proximity to hematopoietic cells in the bone marrow. Recurrent somatic mutations that lead to an expanded population of mutant blood cells is termed clonal hematopoiesis of indeterminate potential (CHIP). Analyzing exome sequencing data from the UK Biobank, we found CHIP to be associated with increased incident osteoporosis diagnoses and decreased bone mineral density. In murine models, hematopoietic-specific mutations in Dnmt3a, the most commonly mutated gene in CHIP, decreased bone mass via increased osteoclastogenesis. Dnmt3a-/- demethylation opened chromatin and altered activity of inflammatory transcription factors. Bone loss was driven by proinflammatory cytokines, including Irf3-NF-κB-mediated IL-20 expression from Dnmt3a mutant macrophages. Increased osteoclastogenesis due to the Dnmt3a mutations was ameliorated by alendronate or IL-20 neutralization. These results demonstrate a novel source of osteoporosis-inducing inflammation.